Prevalence and impact of infant oral mutilation on dental occlusion and oral health-related quality of life among Kenyan adolescents from Maasai Mara - Arthur Kemoli; Hans Gjørup; Marie-Louise Milvang Nørregaard; Mark Lindholm; Tonnie Mulli; Anders Johansson; Dorte Haubek (BMC Oral Health, 2018)
Abstract Background Infant Oral Mutilation (IOM) includes germectomy and early extraction of primary and permanent incisors and canines, primarily in the lower jaw. The aim of the present study was to examine the prevalence and impact of IOM, involving the removal of mandibular permanent incisors and/or canines, on dental occlusion and Oral Health-Related Quality of Life (OHRQoL) among Kenyan adolescents from Maasai Mara. Methods In a cross-sectional study, 284 adolescents (14–18 yrs. of age) participated in an oral examination and an interview, using a structured questionnaire on age, gender, medical history, and IOM practice. For the analysis of the dental occlusion, participants with IOM, in terms of absence of two or more permanent teeth in the mandibular incisor and/or canine tooth segments (IOM group), were compared to participants who had all six incisors and canines present in the oral cavity (control group). OHRQoL was assessed using child perception questionnaire (CPQ11–14). Results The majority of the participants (61%) had been exposed to IOM, among whom 164 (95%) had absence of two mandibular central incisors. More individuals in the IOM group had maxillary overjet exceeding 5 mm than in the control group (50.9% vs. 20%, p <  0.001). Nineteen (11%) subjects in the IOM group had mesial occlusion in contrast to none in the control group (p <  0.001). The mean and median total CPQ scores and the mean and median CPQ domain scores were low in both groups with no significant differences between the groups. Conclusions Approximately two-thirds of the study population presented with IOM, with the majority of them missing two mandibular permanent central incisors. Although some participants with IOM had substantial maxillary overjet and mesial occlusion, only few of them showed substantial effect on their OHRQoL.